Choroidal Infiltration as First Clinical Manifestation of T-cell Large Granular Lymphocyte (T-LGL) Leukemia. (2nd October 2020) - Sarny, Stephanie; Beham-Schmid, Christine; El-Shabrawi, Yosuf
ABSTRACT: Purpose : To report of a 55-year-old woman suffering from choroidal infiltrates as a first clinical manifestation of T-LGL leukemia. Methods : Retrospective case report. Results : A healthy woman presented with photophobia in both eyes since 1 month. She showed a panuveitis with anterior chamber as well as vitreous cells, creamy-white choroidal lesions in both eyes and a cystoid macular edema in the left eye. Lab testing showed only a moderate lymphocytosis, all other tests, including a pars plana vitrectomy and an anterior chamber tap, were negative. Due to the persistent lymphocytosis, she was referred to the oncologist. A biopsy of the bone marrow revealed T-LGL leukemia. A subsequent biopsy of the choroid showed an infiltration of T-LGL and therefore systemic therapy with cyclophosphamide was started. Conclusions : This is a very rare case describing an involvement of the choroid in T-LGL leukemia.